2021
DOI: 10.1108/ijcma-07-2020-0119
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanism linking task conflict with employees’ innovative work behavior

Abstract: Purpose The effect of task conflict on innovative work behavior has yielded inconsistent results pointing to the need to examine the conditions under which task conflict is helpful for employees’ innovative work behavior. This study aims to develop a comprehensive model linking task conflict and innovative work behavior through constructive conflict, positive conflict value, cognitive flexibility and psychological safety. Design/methodology/approach Data were collected from 316 supervisor–subordinate dyads w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 102 publications
(132 reference statements)
0
6
0
Order By: Relevance
“…This finding expands our understanding of work task conflict. Although work task conflict is viewed as a beneficial conflict that stimulates team performance and creativity (Al-Ghazali and Afsar, 2021; Wu et al , 2020) when it comes to well-being consequences, work task conflict is associated with lower work-family balance. The result is also in line with JD-R theory and COR theory suggesting that work task conflict is a job demand that taxes employees’ resources for better managing their work and family lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding expands our understanding of work task conflict. Although work task conflict is viewed as a beneficial conflict that stimulates team performance and creativity (Al-Ghazali and Afsar, 2021; Wu et al , 2020) when it comes to well-being consequences, work task conflict is associated with lower work-family balance. The result is also in line with JD-R theory and COR theory suggesting that work task conflict is a job demand that taxes employees’ resources for better managing their work and family lives.…”
Section: Discussionmentioning
confidence: 99%
“…Extant research consistently shows the destructive influences of work relationship conflict on performance and well-being (de Wit et al , 2012; Kozusznik et al , 2020), but the findings for work task conflict vary and are not consistent. There is substantial evidence showing that work task conflict positively relates to performance (Wu et al , 2020), idea sharing (Todorova et al , 2020), creativity (Li et al , 2018) and innovative behavior (Al-Ghazali and Afsar, 2021). However, the findings have been lacking as well as mixed regarding the role of work task conflict in employees’ well-being (Spector and Bruk-Lee, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…IWB refers to a set of behavioural tasks that help employees develop, promote and implement new and innovative ideas (Al-Ghazali and Afsar, 2021; Bilal et al. , 2019; Zhang and Yang, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The individual employee is concerned about the teammates’ interests and shows respect and comprehension for their different positions. An open-minded environment is created (Al-Ghazali and Afsar, 2021; Hempel et al , 2009), enabling effective cooperation with teammates during a task conflict and creating an environment that supports creativity and innovation (Gelfand et al , 2012). The involved employee also relies on teammates and feels accepted (Tjosvold, 1998), facilitating the sharing and discussion of different ideas, perspectives and viewpoints that become evident in task conflict with teammates.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Our approach is in line with meta-analyses about conflict effects (De Wit et al , 2012; O'Neill et al , 2013) that have shown that it is important to consider moderators that explain when task conflict has beneficial versus dysfunctional effects. According to conflict management scholars, it is not enough to describe the type or degree of conflict; the management of the conflict is decisive to benefit from the potential of conflict in terms of exchanging information and knowledge (Adamovic, 2021; Al-Ghazali and Afsar, 2021). Tjosvold (1998) as well as most prior research distinguishes between two conflict management styles: cooperative conflict management; and competitive conflict management …”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%